How health professionals from basic network identify and treat female urinary incontinence - da Silva Barbosa, Sara; Dolores Reganhan de Oliveira, Léa; Dourado de Almeida Lima, Junia Leonne; Mota de Carvalho, Geraldo; Baena de Moraes Lopes, Maria Helena (O Mundo da Saúde, 2009)
This is a descriptive, exploratory and transversal research that aimed to investigate how doctors and nurses who work in the Basic Health Network approach and care for cases of female urinary incontinence (UI), how they assess it and which types of UI they know. A questionnaire with open and closed questions was used. The variable for characterization of the sample and the answers of the closed questions were descriptively analyzed, and we calculated the relative and absolute frequencies when pertinent. The answers to the open questions were categorized and presented in tables. 37 doctors (family doctors, clinical doctors and gynecologists) and 19 nurses participated of the study, with ages from 24 to 63 years, including recently-formed and experienced professionals. We observed that, except for gynecologists, many professionals rarely investigate rare or do not investigate the possibility of UI. We also observed that professionals ask women about UI, but sometimes the right way to do this is unknown or not always the most adequate.